The Relationship Between Learning Motivation and Critical Thinking on Mathematics Learning Outcomes of Class VIII Students at MTS PP Darussalam - Okviani Syafti; Sefrinal; Meliza Nurnita Sari (Cv. Kilau Rashdan Publishing, 2026)
This study aims to determine whether there is a significant relationship between learning motivation and students' mathematical critical thinking skills at MTs PP Darussalam. The research method used is quantitative correlation. The study population was all students of MTs PP Darussalam, with a sample of 21 students taken using a purposive sampling technique. The research instruments were a learning motivation questionnaire (25 statement items) and a mathematical critical thinking ability test (learning outcome scores). Data analysis used Product Moment correlation. The results of the analysis showed a positive correlation between learning motivation and critical thinking skills. This indicates that the higher a student's learning motivation, the higher their mathematical critical thinking skills.